Use of fiber reinforced concrete in bridges – Metrorrey Line 2 case study. (1st February 2023) - Domingo, Magí; Ramos, Gonzalo; Aparicio, Ángel C.
Highlights: Viaduct redesign using Fiber Reinforced Concrete (FRC) as resisting material. Case study on the replacement of reinforced concrete by FRC. FRC replaces conventional reinforcement in transversally prestressed viaducts. Serviceability reinforcement due to light-train loads is fully eliminated with FRC. FRC improves crack opening for large concrete covers while using ULS reinforcement. Abstract: An assessment concerning the structural applicability and performance of fiber reinforced concrete (FRC) is presented for different bridge elements and within a design framework. FRC as the main bearing material in structural members has evolved from low-demand applications to increasingly ones, where bending and shear are the main internal forces. In actual applications, this was reflected with initial slab-on-grade cases, through tunnels, and later moving towards elevated slabs. Past experiences show that FRC has notable features regarding ultimate capacity and serviceability performance (i.e., enhanced crack control). These capabilities allowed for optimizations such as material savings, reduction of intensive labor during construction, or extended durability. Considering FRC's enhancements from previous applications, a case study based on the Metrorrey Line 2 light-train viaduct (Mexico) is developed. The case study aims to assess the structural performance that FRC can deliver within bridge geometries, loads, and specific conditions. Two numerical models considering different transversal post-tensioning configurations are developed based on the reference structure. The use of these two numerical models aims to broaden the applicability of this study to most U-shaped light-train viaducts. The design is based on current and future standards and recommendations, being prEN1992-1-1:2021, EN1992-1-1:2004, and fib Model Code 2010. After the numerical models and structural analysis, different sectional analyses at ultimate and serviceability levels are carried out, considering both conventional and fiber reinforced concretes. From the sectional results, FRC can provide reductions to reinforcement quantities at ultimate load levels, which are tied to the initially required reinforcement ratio (in other words, linked to the internal forces existing in the element). When higher reinforcement ratios are necessary, FRC optimizations point toward serviceability limit states, especially on the crack width reduction and the potential to reduce or suppress any additional reinforcement due to crack limitations.